2012
DOI: 10.1016/j.ygyno.2012.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic testing on endometrial cancer risk-reducing practices in women at risk for Lynch syndrome

Abstract: OBJECTIVE Due to the increased lifetime risk of endometrial cancer (EC), guidelines recommend that women with Lynch syndrome (LS) age ≥35 undergo annual EC surveillance or prophylactic hysterectomy (PH). The aim of this study was to examine the uptake of these risk-reducing strategies. METHODS The study population included women meeting clinical criteria for genetic evaluation for LS. Data on cancer risk-reducing behaviors were collected from subjects enrolled in two distinct studies: (1) a multicenter cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…The authors concluded that excluding TAH/BSO would have little effect for female probands and mutation carriers, but would substantially reduce costs, thus leading to a lower ICER. Economic analyses specific to gynecologic cancers in LS have concluded that TAH/BSO is likely to be highly cost-effective [ 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that excluding TAH/BSO would have little effect for female probands and mutation carriers, but would substantially reduce costs, thus leading to a lower ICER. Economic analyses specific to gynecologic cancers in LS have concluded that TAH/BSO is likely to be highly cost-effective [ 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Screening recommendations are less clearly established for associated GC, with a suggestion that women should consider starting annual pelvic ultrasounds with endometrial sampling between 30 and 35 years of age for the detection of endometrial cancer, however the evidence of benefit is weak [10]. To date, no benefit has been shown for ovarian cancer screening [11]. The only effective intervention to reduce the risk of GC in women is prophylactic hysterectomy and bilateral salphingo-oophorectomy (BSO) from age 40 years, or once they have completed childbearing [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that LS carriers were compliant with guidelines for cancer risk reduction in the year following genetic testing, with nearly 70% opting for prophylactic hysterectomy by three-year follow up [ 17 ]. Research suggests prophylactic surgery decisions are complex, driven by demographics (e.g., age, parity), medical factors (e.g., mutation status or abnormal ovarian screening results) and psychosocial factors (e.g., anxiety about cancer risk) [ 14 ]-[ 18 ].…”
Section: Introductionmentioning
confidence: 99%